Preparing an orthopedic department for COVID-19: Lessons learned from reorganization and educational activities - Rune Dall Jensen; Magnus Bie; Anne Plønd Gundsø; Johannes Martin Schmid; Joachim Juelsgaard; Maria Louise Gamborg; Hanne Mainz; Jan Duedal Rölfing (Acta Orthopaedica, 2020)
Background and purpose — The COVID-19 pandemic has disrupted healthcare services around the world. We (1) describe the organizational changes at a level 1 trauma center, (2) investigate how orthopedic healthcare professionals perceived the immense amount of information and educational activities, and (3) make recommendations on how an organization can prepare for disruptive situations such as the COVID-19 pandemic in the future. Methods — We conducted a retrospective survey on the organizational restructuring of the orthopedic department and the learning outcomes of a needs-driven educational program. The educational activities were evaluated by a non-validated, 7-item questionnaire. Results — The hospital established 5 COVID-19 clusters, which were planned to be activated in sequential order. The orthopedic ward comprised cluster 4, where orthopedic nursing staff were teamed up with internal medicine physicians, while the orthopedic team were redistributed to manage minor and major injuries in the emergency department (ED). The mean learning outcome of the educational activities was high–very high, i.e., 5.4 (SD 0.7; 7-point Likert scale). Consequently, the staff felt more confident to protect themselves and to treat COVID-19 patients. Interpretation — Using core clinical competencies of the staff, i.e., redistribution of the orthopedic team to the ED, while ED physicians could use their competencies treating COVID-19 patients, may be applicable in other centers. In-situ simulation is an efficient tool to enhance non-technical and technical skills and to facilitate organizational learning in regard to complying with unforeseen changes.